Sağlık Çalışanlarında Mesleki Tükenme: Görsel Haritalama Tekniği ile Bibliyometrik Bir Analiz. - ÖZEN, Melek Yağcı; UYAR, Seda (Journal of Abant Social Sciences / Abant Sosyal Bilimler Dergisi, 2025)
In this study, the aim is to examine the changes in research on occupational burnout among healthcare workers and studies related to occupational burnout over the years. In this context, studies conducted on occupational burnout among healthcare workers between 1998 and 2022 were included in the research using the "Web of Science" database. VOSviewer program was used to access bibliometric profiles and visual mapping findings of the included studies. The research illustrates the most productive authors, institutions, most cited authors, and collaborations among authors in the context of occupational burnout specifically among healthcare workers. Keyword analyses revealed that communication, behavior, palliative care, end-of-life care, Covid-19, and nursing practices were prominent concepts in relation to occupational burnout among healthcare workers. After 2018, telemedicine, quality improvement, digitalization, depression, evidence-based practices, and patient safety emerged as important concepts in publications.